PRESERVATION AND POPULARISATION OF ARTEMII VEDEL’S CHORAL HERITAGE BY THE UKRAINIAN DIASPORA (to the 250th birthday anniversary) - Карась, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper highlights the figure of Artemii Vedel, an outstanding Ukrainian composer, and his creative work in the cultural and artistic reflections of the Ukrainian diaspora in the XXth century. The attention is focused on the representation of three vectors: the performance of A. Vedel’s choral heritage outside Ukraine; scientific researches and opinion journalism about the composer; preservation and publications of his choral works. The source basis for the research is discovered and analysed – publications of music culture leaders and opinion journalists of the Ukrainian diaspora, printed music. The performance of Artemii Vedel’s choral heritage in different countries of the world throughout the XXth century witnesses to its topicality in the choral process, the Ukrainian composer’s high achievements in the realm of spiritual music. Scientific researches on the composer were conducted by Oleksandr Koshyts, Vasyl Vytvytskyi and Ihor Sonevytskyi. Preservation and publication of A. Vedel’s choral works are connected with the names of Vasyl Zavitnevych, Ihor Sonevytskyi and Volodymyr Kolesnyk. It is discovered that in spite of the lack of any state support of its culture, scatteration and other objective circumstances, the Ukrainian diaspora made a significant contribution to the commemoration of the outstanding Ukrainian composer Artemii Vedel, preservation and popularisation of his choral heritage.